Calculation of the invested capital profitability in the financial condition analysis process - et al., Khasanov Bakhodir Akramovich (International Journal of Advanced Science and Technology, 2019)
The article examines the issues of calculating the return on invested capital according to the financial statements. Proposals are given to implement the results of the methodology on the practice of joint- stock companies. The use of the method of factor analysis in this direction when calculating the profitability of capital investments based on financial data used in developed foreign countries has a positive result. In particular, the increase in profits under the influence of the factor of turnover of capital and profitability of income allows you to calculate the return on investment.